Clinical features of rheumatoid arthritis. (April 2018) - Gulati, Malvika; Farah, Ziad; Mouyis, Maria
Abstract: Rheumatoid arthritis (RA) is a multiorgan chronic inflammatory condition that affects 0.84% of the UK population. The cardinal clinical feature is a symmetrical polyarthritis that predominantly affects the small joints. RA can affect other components of the musculoskeletal system (bursitis, tendinopathy, muscle atrophy, osteoporosis) and almost every organ in the body. Extra-articular manifestations of RA can be cutaneous, haematological, neurological, pulmonary, cardiac, renal and ocular. A better understanding of the varied clinical aspects of RA is vital to instigating appropriate management. This review provides a detailed description of the clinical manifestations of RA, both musculoskeletal and extra-articular.